Effect of H-bonding effect on reverse micelle extraction of bovine serum albumin. Issue 14 (1st December 2020) - Ma, Mengyuan; Song, Jian; Bai, Lichen; Wei, Guan; Dai, Jianfeng; Chen, Zhiyun; Yin, Tianxiang
Abstract: The extraction of bovine serum albumin (BSA) was carried out by using reverse micelles formed by cationic surfactant dodecyltrimethylammonium bromide (DTAB), N -dodecyl- N -2-hydroxyethyl- N, N -dimethyl-ammonium bromide (HDAB) and N -dodecyl- N, N -2-dihydroxyethyl- N -methyl ammonium bromide (DHAB). The factors like pH, surfactant concentration, salt concentration, and co-solvent concentration were investigated. The good maintenance of the secondary structure of BSA after extraction was confirmed by UV spectra. A wider aqueous phase pH range was achieved and less amount of surfactant was needed on efficient forward extraction when hydroxyethyl group was presented in the surfactants' head group, suggesting an important role of H-bonding effect. At lower pH or high salt concentration, reasonable backward extraction efficiencies were observed in all systems. The little difference of the head group of these surfactants resulted in quite different performance in the extraction process, which provided deeper insight on the effect of fine adjustment of surfactant structure on protein extraction. Graphical Abstract: uf0001